The combustion behavior of diesel/CNG mixtures in a constant volume combustion chamber - Firmansyah, (Institute of Physics Publishing, 2015)
The stringent emissions and needs to increase fuel efficiency makes controlled auto-ignition (CAI) based combustion an attractive alternative for the new combustion system. However, the combustion control is the main obstacles in its development. Reactivity controlled compression ignition (RCCI) that employs two fuels with significantly different in reactivity proven to be able to control the combustion. The RCCI concept applied in a constant volume chamber fueled with direct injected diesel and compressed natural gas (CNG) was tested. The mixture composition is varied from 0 - 100 diesel/CNG at lambda 1 with main data collection is pressure profile and combustion images. The results show that diesel-CNG mixture significantly shows better combustion compared to diesel only. It is found that CNG is delaying the diesel combustion and at the same time assisting in diesel distribution inside the chamber. This combination creates a multipoint ignition of diesel throughout the chamber that generates very fast heat release rate and higher maximum pressure. Furthermore, lighter yellow color of the flame indicates lower soot production in compared with diesel combustion.